Effect of selenium nanoparticles on intestinal immunity through regulation of NLRP3 signaling pathway - Zhengtian Li; Irfan Ahmed; Lin Chen; Sikandar Ali; Syed Khurram Fareed; Roshan Riaz; Hemei Yuan (Scientific Reports)
Abstract This research delves into the intricate mechanisms by which Selenium nanoparticles exert their influence on intestinal health, with a focus on the modulation of NLR family pyrin domain containing 3 (NLRP3) signaling pathway. Therefore, 150 chicks were divided into three groups, which were control group, 0.2 mg/kg (low dose) and 0.4 mg/kg (high dose) Selenium nanoparticles (SeNPs) for 1 month respectively. This study showed that selenium nanoparticles effectively reduced the mortality rate of chickens. Morphological intestinal parameters were significantly reduced with increased dose of Selenium nanoparticles compared to low dose. The number of goblet cells were significantly decreased with a high dose of SeNPs. As well, the mRNA expression of Mucin2 (Muc2) significantly decreased. Compared with control group the positivity of apoptosis in the intestinal cells significantly decreased in SeNPs groups. Likewise, with high dose of SeNPs the protein and gene expression levels of Bcl-2-associated X (Bax), Caspase-3 and B-cell lymphoma-2 (Bcl-2) in small intestine significantly decreased. High dose of SeNPs significantly decreased oxidative stress and inflammation in the small intestine. High dose of SeNPs significantly decreased the toll-like receptor-2 (TLR-2), NLRP3, claudin-5 and zonula occluden-1 (ZO-1) in small intestine. The integration of scientific evidence and experimental insights will contribute to a deeper understanding of the intricate interplay between SeNPs and intestinal health, offering valuable perspectives for future research and therapeutic applications.